Microstructure and chemical composition of the oxide scale formed on the sanicro 25 steel tubes after fireside corrosion. (January 2016) - Rutkowski, Bogdan; Gil, Aleksander; Czyrska-Filemonowicz, Aleksandra
Highlights: Cr2 O3 scale having tens nanometer sized grains was formed on Sanicro 25 at 650 °C. M23 C6 carbides was thermodynamically unstable in Cr-depleted zone. Beneath the Cr2 O3 a layer with short-range ordering typical for glass was formed. Nanometer sized Cu-rich particles were precipitated from the austenitic matrix. Abstract: The Sanicro 25 austenitic steel is foreseen as a potential material for steam superheaters and reheaters in ultra-supercritical power plants. The aim of investigation was to characterize in detail an oxide scale grown on the Sanicro 25 tube after fireside oxidation at 650 °C. The morphology of the oxide scale and the microstructure of the bulk material were investigated using advanced electron microscopy methods. A multilayered and multicomponent oxide scale containing mainly Cr2 O3 was found on the surface exposed to combustion gases. Directly under the oxide scale, a chromium-depleted zone with no M23 C6 carbides was observed.